2010
DOI: 10.1007/s00247-010-1744-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-related variations in white matter anisotropy in school-age children

Abstract: Age effects on FA and variability in FA are location-dependant in developing WM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…Despite a trend of the greatest rate of age-dependent changes occurring in FA in rostral ROIs, statistically significant differences were noted only between the ALIC and PLIC and in the MD between the genu of the CC and splenium of the CC. These results detected in the CC and internal capsule also correlate with other studies 19,28,31,32 demonstrating a conspicuous acceleration in myelination in the anterior regions of the respective WM tracts from the fourth to the eighth postnatal month.…”
Section: Differences In Developmental Timing and Regional Pattern Of supporting
confidence: 90%
“…Despite a trend of the greatest rate of age-dependent changes occurring in FA in rostral ROIs, statistically significant differences were noted only between the ALIC and PLIC and in the MD between the genu of the CC and splenium of the CC. These results detected in the CC and internal capsule also correlate with other studies 19,28,31,32 demonstrating a conspicuous acceleration in myelination in the anterior regions of the respective WM tracts from the fourth to the eighth postnatal month.…”
Section: Differences In Developmental Timing and Regional Pattern Of supporting
confidence: 90%
“…Also during the here examined childhood period (as well as during later adolescence and young adult age), increase in myelination appears to be the likely microstructural substrate of the observed macrostructural increase. This notion is supported by diffusion-tensor imaging studies showing increase in callosal fractional anisotropy during childhood and adolescence (e.g., Krogsrud et al, 2016;Lebel et al, 2008;Rollins et al, 2010;Snook et al, 2007). Crucially, the increase in anisotropy appears to be mainly driven by a reduction in radial diffusion, i.e.…”
Section: Discussionmentioning
confidence: 80%
“…Crucially, the increase in anisotropy appears to be mainly driven by a reduction in radial diffusion, i.e. diffusion orthogonal to the main fiber direction (e.g., Krogsrud et al, 2016;Rollins et al, 2010), which is likely indicative for an increased in myelination of the axons (Song et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Potential contributions of iron-deposition that decrease T2 relaxation time may also be considered, particularly in the deep gray nuclei, which has been observed in children older than 4 years of age and in adolescents. 36 Although various studies have reported ADC changes of cerebral white matter in children, [12][13][14] gray matter structures have remained relatively unexplored. We observed a steep decline with an exponential component in early childhood with a decreasing trend continuing into later childhood, consistent with results of prior ROI-based studies in selected deep gray regions (caudate, putamen, globus pallidus).…”
Section: Discussionmentioning
confidence: 99%
“…11 Various studies have examined apparent diffusion coefficient changes of white matter in children. [12][13][14] However, at present, the ADC of the gray matter, notably at the cortical level, is not welldocumented. While volumetric and diffusion analysis can be used to probe macro-and microstructural changes, respectively, arterial spinlabeling (ASL) cerebral blood flow is increasingly used clinically to obtain advanced physiologic information.…”
mentioning
confidence: 99%